(untitled) (Development Service Industry Management, 2025)
The article is dedicated to the study of capsule hotels as a modern trend in the hospitality industry, using the example of the capsule hotel «Constellation 89» in Lviv. The research examines the history of capsule hotels, their concept, key characteristics, and identifies the advantages and disadvantages of this type of accommodation. It was found that the benefits of capsule hotels, such as affordability, cost-effectiveness, convenience for travelers, and quick service, significantly outweigh their drawbacks, which include limited space and lack of privacy. These disadvantages are important for defining the target audience and further development strategies for such hotels. The article provides a detailed analysis of the operations of «Constellation 89», including an assessment of its financial and economic performance, management efficiency, and investment activities. To identify the hotel’s strengths, weaknesses, opportunities, and threats, a SWOT analysis was conducted, highlighting strong points such as high profitability and adaptability to market changes, while also revealing potential threats like economic fluctuations and intense competition. However, leveraging opportunities for service diversification, improving marketing strategies, and enhancing infrastructure can ensure the sustainable development of the hotel in the future. Based on the findings, the study proposes innovative projects, including the integration of automated service systems, the development of new services, and the strengthening of marketing strategies through an active online presence and collaboration with international booking platforms. These initiatives aim to attract new audiences and increase the loyalty of existing clients. Thus, in exploring the current state and development trends of capsule hotels, the research outlines ways to shape their concept as a budget-friendly and comfortable accommodation option for short-term tourists, positioning them as a promising direction for innovative growth in Ukraine’s tourism industry.